The behaviour of jointed large-diameter reinforced concrete pipeline buried in various ground conditions. (15th December 2017) - Xu, Ming; Shen, Dawei; Jin, Dehai
Highlights: Both centrifuge test and three-dimensional numerical simulation were performed. Reasonable agreement was found between the computed and centrifuge test results. The foundation stiffness had much larger impact than the gasket stiffness. Parametric studies of pipeline buried in various ground conditions were performed. The existence of voids under the joint could cause severe pipeline deformation. Abstract: Both centrifuge test and three-dimensional numerical simulation were performed to investigate the behaviour of a 1400-mm-diameter reinforced concrete pipeline with gasketed bell-and-spigot joints that was buried in various ground conditions under surface load. Centrifuge test was performed first to study the response of a pipeline placed on silt soil. Numerical simulation was then carried out using a nonlinear elastic-plastic model to represent the soils, with parameters being back-analysed from direct shear tests, which was found to be capable of producing reasonable predictions when compared with the centrifuge test results. Further simulation revealed that the native soil stiffness had a dominant influence on the joint behaviour compared with the backfill stiffness. For the same trench dimensions, increasing the foundation thickness was less effective at reducing the joint rotation than increasing the cover depth. Furthermore, as long as the native soil below the pipeline was uniform, the joint rotation was small, even though the native soil was soft. However, the existence of voids due to soil erosion under the joint had a significant impact on the pipeline performance and could cause a large joint rotation.